Effectiveness and safety of azvudine in the treatment of COVID-19 patients: a retrospective cohort study using propensity score matching - Jing Zhang; Fang Wang; Ying Xie; Qianyu Li; Zhenzhen Zhu; Yuan Dong (Frontiers in Cellular and Infection Microbiology)
BackgroundClinical trials have demonstrated the efficacy of azvudine in alleviating clinical symptoms among patients with coronavirus disease 2019 (COVID-19). However, evidence regarding its real-world effectiveness and safety profile remains limited.ObjectiveTo evaluate the effectiveness and safety of azvudine in COVID-19 patients.MethodsThis retrospective cohort study included 192 COVID-19 patients hospitalized in Fengtai District, Beijing, from November 1 to December 31, 2022. Patients were divided into azvudine (n=118) and non-azvudine (n=74) groups. Propensity score matching (PSM) was applied to balance baseline characteristics (age, sex, vaccination status, etc.), yielding 48 matched pairs. Outcomes included time to SARS-CoV-2 RNA negativity, hospitalization duration, and symptom resolution (fever, cough). Adverse events were recorded.ResultsAfter PSM, 48 pairs of COVID-19 patients were identified. The azvudine group exhibited significantly shorter hospitalization than the non-azvudine group (median: 8 vs. 10 days, P ≤ 0.05). No significant differences were observed in time to RNA negativity (4.23 vs. 4.52 days, P>0.05), fever duration (2 vs. 2 days, P>0.05), or cough duration (4.5 vs. 5 days, P>0.05). One case of mild gastrointestinal discomfort was reported in the azvudine group.ConclusionAzvudine significantly reduced hospitalization duration in mild-to-moderate COVID-19 patients with a favorable safety profile.